2022
DOI: 10.3390/children9010104
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Surgency, Behavioral Inhibition, Negative Emotionality and Effortful Control in the Relationship between Parenting Style and Children’s Reactive and Proactive Aggression

Abstract: The principal aim of this study is to explore the moderating role of temperament in the relationship between parenting style and the reactive and proactive aggressive behavior of 8-year-old children. The participants are 279 children (154 boys and 125 girls). To measure reactive and proactive aggression, children completed the reactive and proactive questionnaire (RPQ). Child temperament and parenting styles were evaluated by both parents using the temperament in middle childhood questionnaire (TMCQ) and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…One study concluded that authoritarian parents considered their children difficult to handle [23]. High levels of surgency and more aggressive behavior were common in children with authoritarian fathers [25]. Aggressive and hostile behavior toward peers is a result of emotional and behavioral maladjustment [26].…”
Section: Discussionmentioning
confidence: 99%
“…One study concluded that authoritarian parents considered their children difficult to handle [23]. High levels of surgency and more aggressive behavior were common in children with authoritarian fathers [25]. Aggressive and hostile behavior toward peers is a result of emotional and behavioral maladjustment [26].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the particular focus of this study was on the identification of children’s and adolescents’ profiles of reactive and proactive aggression and the stability of those profiles over six months, but not on the potential predictors and outcomes of these profiles. An interesting research question is, in particular, which familial factors play the most important role in the prediction of the four subtypes of reactive and proactive aggression, such as parental assistance with emotion regulation in early childhood or parental encouragement of aggressive behavior in adolescence [ 20 , 61 , 63 ]. In summary, further research is needed to reveal the possible precursors and outcomes of children’s and adolescents’ profiles based on the four subtypes of reactive and proactive aggression using more heterogenous samples and considering a larger time period or more than two measurement points.…”
Section: Discussionmentioning
confidence: 99%
“…In all that manner, parenting style and parental control have important effect and it is very necessary to improve the quality of life of a student and also significant to fulfil emerging needs of student. (Del Puerto-Golzarri et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%